Assessing integrated social-emotional and cognitive competencies in pre-service teachers: scale development - Joy D. Talens (Institute of Advanced Engineering and Science, 2026)
Developing integrated social-emotional and cognitive (ISEC) competencies is essential for pre-service teachers (PST), yet these competencies are often underemphasized in teacher education programs. This study aimed to develop and provide preliminary evidence for a reliable, structurally sound instrument to measure ISEC competencies among PST. Using a design and development research approach, PST-ISEC learning competency scale was developed and examined for internal structure and reliability. An initial pool of 74 items, refined through literature review, and expert validation, was administered to purposively selected PST from higher education institutions in one Philippine region (n=370 for exploratory factor analysis (EFA); n=405 for confirmatory factor analysis (CFA)). EFA with Varimax rotation reduced the scale to 22 items across five dimensions: collaborative spirit (CS), hopeful mindset (HM), mindful confidence (MC), emotional resilience (ER), and responsible decision-making and accountability (RD). CFA confirmed five-factor structure with acceptable fit, and internal consistency indices indicated adequate reliability. Convergent and discriminant validity analyses supported construct distinctiveness. The PST-ISEC scale provides a theoretically grounded tool for formative assessment, program evaluation, and targeted interventions. Future studies should examine criterion-related and predictive validity, measurement invariance, and cross-context applicability to strengthen its utility.